2002
DOI: 10.1002/ejsp.118
|View full text |Cite
|
Sign up to set email alerts
|

Social identity, relative group status and intergroup attitudes: when favourable outcomes change intergroup relations…for the worse

Abstract: This study examines in a natural setting (N ¼ 253) the effects of favourable outcomes at the individual and group levels on the relations between members of high (nondisabled) and low (disabled) status groups. Consistent with past research, the results show that, overall, high-status group members are more likely than low-status group members to display ingroup bias. Furthermore, as hypothesized on the basis of the role of relative gratification in intergroup relations, a favourable group outcome led high-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 64 publications
5
43
1
3
Order By: Relevance
“…This process interacts with group status (see Bettencourt, Door, Charlton, & Hume, 2001 for review). Namely, high-status group members almost systematically favor their own group and sometimes derogate the outgroup, whereas low-status group members often exhibit outgroup favoritism, i.e., favoring the high-status group (Brown, 1995, for review;Guimond, Dif, & Aupy, 2002). On this basis, authors (Dubois & Beauvois, 1996;Dubois, Beauvois, Gilibert, & Zentner, 2000;Pansu et al, 2005) have considered that, as people tend to attribute more positive judgments to their ingroup in equivalent intergroup relations, then a judgment systematically attributed to an ingroup should be considered socially valued.…”
Section: Intergroup Biases As Indicators Of the Social Valorization Omentioning
confidence: 99%
“…This process interacts with group status (see Bettencourt, Door, Charlton, & Hume, 2001 for review). Namely, high-status group members almost systematically favor their own group and sometimes derogate the outgroup, whereas low-status group members often exhibit outgroup favoritism, i.e., favoring the high-status group (Brown, 1995, for review;Guimond, Dif, & Aupy, 2002). On this basis, authors (Dubois & Beauvois, 1996;Dubois, Beauvois, Gilibert, & Zentner, 2000;Pansu et al, 2005) have considered that, as people tend to attribute more positive judgments to their ingroup in equivalent intergroup relations, then a judgment systematically attributed to an ingroup should be considered socially valued.…”
Section: Intergroup Biases As Indicators Of the Social Valorization Omentioning
confidence: 99%
“…Displays of ingroup favoritism and outgroup derogation are most common among members of advantaged rather than disadvantaged groups (Guimond, Dif, & Aupy, 2002;Sidanius, Pratto, Martin, & Stallworth, 1991). Even though legislative changes in recent history have given rise to the social consensus that discrimination is morally objectionable (Plant & Devine, 1998), more subtle, indirect forms of discrimination and 3…”
Section: Opposition To Social Equality and Group Positionmentioning
confidence: 99%
“…The identity problem of high status groups is generally more to maintain than to obtain a positive social identity (e.g. Guimond et al, 2002). In a direct demonstration of social identity threat, Scheepers and Ellemers (2005) showed that social identity threats do not only occur in low status groups, but also in high status groups when the possibility is made salient that the group may lose its relative advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this has been explained as a result of the fact that intergroup comparisons between low-and high-status groups will enhance or maintain positive social identity only among members of the latter (Tajfel & Turner, 1986). While not being identical with high status, high power is an equivalent concept 3 which, in some studies, has turned out to eliminate the PNAE (Amiot & Bourhis, 2005a;Guimond, Dif, & Aupy, 2002).…”
Section: Group Status As Vitality and As A Predictor Of Intergroup Biasmentioning
confidence: 99%